Organisation and management of literacy programmes (2018)
Organisation and management of literacy programmes are very germane to the success of literacy delivery. It is against this background that this paper examined strategies that Nigeria needs to put in place for the revitalization of literacy programmes. The paper concluded that for education to enrich an individuals’ knowledge and develop his/her potentials to prepare for future challenges in an ever-changing world, education, particularly literacy, ought to be effectively and efficiently organised and managed